The Effect of Variations in Flexibility Training on the Service Ability of Bengkulu University Sepak Takraw Athletes - Barnanda Rizky, Oddie; Defliyanto, Defliyanto; Yarmani, Yarmani; Tri Fitrianto, Ari (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2024)
This study aims to determine the effect of variations in flexibility training on the sepak takraw service abilities of Bengkulu University sepak takraw athletes. This type of research is quantitative. The population in this study were 30 athletes who took part in sepak takraw UKM at Bengkulu University. The research design used was one group pre test-post test. The sampling technique used was total sampling. The number of samples in this study was 30 athletes. The treatment given is a variety of flexibility exercises. The data collection technique in this research uses a direct test method, namely using the sepak takraw service ability test. The statistical requirements test meets the homogeneity requirements and the data is normally distributed based on statistical calculations for experimental group one. The results obtained from the analysis results obtained from the t-test show that the data has a significant value of 0.000 < 0.005 which can be concluded that there is an influence if compared, then ha is accepted. The results of this research show that there is an influence between variations in flexibility training on the sepak takraw service ability of Bengkulu University sepak takraw athletes so that it can influence the improvement of sepak takraw service ability and can be used as a training method to improve athlete performance.